Association of IL1Β (-511 A/C) and IL6 (-174 G > C) polymorphisms with higher disease activity and clinical pattern of psoriatic arthritis. Issue 7 (July 2016) - Cubino, N.; Montilla, C.; Usategui-Martín, R.; Cieza-Borrela, C.; Carranco, T.; Calero-Paniagua, I.; Quesada, A.; Cañete, J.; Queiro, R.; Sánchez, M.; Hidalgo, C.; Martínez, O.; et al.
Abstract The objective of this study is to analyze whether IL1β (-511G > A) and IL6 (-174 G > C) polymorphisms are associated with inflammatory activity, radiographic damage or clinical pattern of psoriatic arthritis (PsA). One hundred twenty-five patients classified as PsA according to the Classification of Psoriatic Arthritis (CASPAR) criteria were included. Patients were stratified according to their clinical pattern at inclusion as peripheral, axial, or mixed involvement. Disease activity in peripheral or mixed forms was measured using the number of swollen and tender joints, pain analog visual scale, erythrocyte sedimentation rate (ESR), C-reactive protein (CRP), and disease activity score 28 (DAS28). Bath Ankylosing Spondylitis Disease Activity Index (BASDAI) was used for axial and mixed forms, as were pain visual analog scale, ESR and CRP. Radiographic damage was evaluated using a modified Sharp score and modified stoke ankylosing spondylitis spinal score (SASSSm). The polymorphisms for the promoter region of IL1β (-511 G/A) and IL-6 (-174 G/C) were analyzed. The G allele of IL1B (-511G/A) polymorphism was associated with higher peripheral joint disease activity (OR 3.13;p  < 0.0004; CI 95 % 1.43–6.82, p (corrected) <0.008), while the G allele of the IL6 (174G > C) polymorphism presented a strong trend to be associated with peripheral forms (70.86 %) (OR 1.89;p  < 0.03; CI 95 % 1.06–3.39, p -corrected 0.05). In addition, this allele showed a lower association with HLA-B27 (15.78 %) compared with C allele (28.57 %) (OR 0.469;p  = 0.02; CI 95 % 0.238–0.923, p -corrected 0.03). This study suggests that the G allele polymorphism of IL1B (-511 A/C) is associated with higher peripheral joint disease activity. On the other hand, the IL6 (-174 G/C) polymorphism showed a strong trend to be associated with the peripheral pattern of PsA.